Adapting Hearing Devices to the Individual Ear Acoustics: Database and Target Response Correction Functions for Various Device Styles. (June 2018) - Denk, Florian; Ernst, Stephan M. A.; Ewert, Stephan D.; Kollmeier, Birger
To achieve a natural sound quality when listening through hearing devices, the sound pressure at the eardrum should replicate that of the open ear, modified only by an insertion gain if desired. A target approximating this reference condition can be computed by applying an appropriate correction function to the pressure observed at the device microphone. Such Target Response Correction Functions (TRCF) can be defined based on the directionally dependent relative transfer function between the location of the hearing device microphone and the eardrum of the open ear. However, it is unclear how exactly the TRCF should be derived, and how large the benefit of individual, versus generic, correction is. We present measurements of Head-Related Transfer Functions (HRTF) at the eardrum and at 9 microphone locations of a comprehensive set of 5 hearing device styles, including 91 incidence directions, and recorded in 16 subjects and 2 dummy heads. Based on these HRTFs, individualized and generic TRCF were computed for frontal (referred to as free-field) and diffuse-field sound incidence. Spectral deviations between the computed target and listening with the open ear were evaluated using an auditory model and virtual acoustic scenes. Results indicate that a correction for diffuse-field incidence should be preferred over the free field, and individual correction functions result in notably reduced spectral deviations to open-ear listening, as compared with generic correction functions. These outcomes depend substantially on the specific device style. The HRTF database and derived TRCFs are publicly available.